Fenugreek (Trigonella foenum-graecum) Sprout Extract for Diabetes Management in Streptozotocin Induced Rat Model (Journal of Bio-Science, 2026)
Diabetes mellitus is a widespread metabolic disorder marked by persistent high blood sugar due to inadequate insulin secretion or action. While conventional antidiabetic drugs are available, their side effects have led to the exploration of alternative treatments. Fenugreek (Trigonella foenum-graecum) is noted for its medicinal properties, particularly in managing diabetes. In this study, fenugreek seeds were sprouted, and methanolic extracts were prepared. Diabetes was induced in Long-Evans rats through streptozotocin (STZ) injection, and diabetic rats were treated with fenugreek sprout extract at a dosage of 400 mg/kg body weight per day for 28 days. Blood glucose levels (BGL) were regularly monitored, and pancreatic tissues were examined histologically to assess the protection of β-cells. The fenugreek sprout extract demonstrated significant antidiabetic effects, as the treated rats exhibited a notable reduction in blood glucose levels (BGL) compared to diabetic control groups (both positive and negative). Histopathological examination revealed that the pancreatic β-cells of fenugreek-treated rats were protected, exhibiting improved morphology and reduced immune cell infiltration. The study aimed to investigate the antidiabetic potential of methanolic extracts of fenugreek sprouts in STZ-induced diabetic Long-Evans rats. The results suggest that fenugreek sprouts have antidiabetic properties, offering a natural alternative for diabetes management.J. Bio-Sci. 33(1): 31-40, 2025